2019
DOI: 10.19136/era.a7n1.2059
|View full text |Cite
|
Sign up to set email alerts
|

Composición de comunidades y filoespecificidad de ectoparásitos de murciélagos en paisajes agropecuarios de Veracruz, México.

Abstract: Composición de comunidades y filoespecificidad de ectoparásitos de murciélagos en paisajes agropecuarios de Veracruz, México.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…When we excluded data from Orta‐Pineda et al ( 2020 ; see Materials and Methods), we found a weaker overall effect of forest fragmentation on all parasite outcomes. Roost duration was still an important and significant predictor for prevalence.…”
Section: Resultsmentioning
confidence: 77%
See 4 more Smart Citations
“…When we excluded data from Orta‐Pineda et al ( 2020 ; see Materials and Methods), we found a weaker overall effect of forest fragmentation on all parasite outcomes. Roost duration was still an important and significant predictor for prevalence.…”
Section: Resultsmentioning
confidence: 77%
“…One study in our analysis provided a unique description of the habitats that were sampled; all sites experienced some degree of fragmentation, but some could still be considered continuous forest depending on when the land was last cleared (Orta‐Pineda et al, 2020 ). After excluding this study from our meta‐analysis, we observed similar results for the moderator variables (notably, the wing aspect ratio was still an important predictor for all outcomes), yet the overall effects of forest type on parasite outcomes were weaker.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations